Rare bird documentation form for Northern Goshawk at Ulrich Park, 1981 - Moore, Francis L.et al (1981)
Rare bird documentation form for a Northern Goshawk at Ulrich Park in Black Hawk County, IA on December 25, 1981. Epson - sheet feed